PENGARUH SUHU DAN PENAMBAHAN BAHAN ABRASIVE KULIT ARI BIJI KAKAO TERHADAP KARAKTERISTIK KRIM BODY SCRUB - Giri Natha, Anak Agung Gede Rai; Wiranatha, A.A.P. Agung Suryawan; Mulyani, Sri (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2019)
The aims of this study were: 1) to determine the effect of temperature and the addition of abrasive ingredients on the epidermis of cocoa beans to the characteristics of body scrub creams, and  2) to obtain temperature and the addition of abrasive ingredients to the epidermis of cocoa beans to produce the best characteristic body scrub cream, and 3)  how the quality of body scrub cream changes during storage. The experimental design used in this study was a factorial randomized block design, which consisted of 2 factors. The first factor was the heating temperature which consists of two levels, namely temperature of 65 °C and 75 °C. The second factor was the addition of abrasive materials which consists of three levels namely 3 percent, 6 percent and 9 percent. All treatments were grouped into 3 groups to obtain 18 experimental units. The data obtained were analyzed by variance and  the Duncan test. The best result of body scrub cream is the treatment of heating temperature 65°C and the addition of powder epidermis of cocoa beans 9 percent  with the characteristics of pH 5.53, viscosity of 36,627 cp, content of phenolic compounds 21.631 mg GAE/g, aroma 5.85 and passions 5.55. pH, viscosity and total phenolic compounds are stable up to 6 weeks of storage. Keywords : epidermis of cocoa beans, body scrub, characteristic, temperature, addition of abrasives